The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/cdev.12454
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sensitivity and Child Secure Base Use in Early Childhood: Studies in Different Cultural Contexts

Abstract: This study tested whether maternal sensitivity and child security are related during early childhood and whether such an association is found in different cultural and social contexts. Mother-child dyads (N = 237) from four different countries (Colombia, Mexico, Peru, and the United States) were observed in naturalistic settings when children were between 36 and 72 months of age. Maternal and child behavior during interactions at home and in the playground were described using Q methodology. Findings reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
22

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 57 publications
1
45
1
22
Order By: Relevance
“…Our last question was concerned with whether maternal co-construction skills add unique information to the prediction of children's security at both times above and beyond the contributions of maternal sensitivity. Consistent with previous studies using preschool samples (e.g., Posada et al, 2016), and as reported in Study 1, Chapter III (this monograph), children's secure base use was significantly associated with sensitive caregiving at Time 1 (r[79] ¼ 0.36, p < .001) and Time 2 (r[67] ¼ 0.34, p ¼ .003), after controlling for children's gender-the associations were virtually the same without controlling for gender, r(80) ¼ 0.38, p < .001 at Time 1; r(68) ¼ 0.36, p ¼ .002 at Time 2.…”
Section: Main Analysessupporting
confidence: 91%
“…Our last question was concerned with whether maternal co-construction skills add unique information to the prediction of children's security at both times above and beyond the contributions of maternal sensitivity. Consistent with previous studies using preschool samples (e.g., Posada et al, 2016), and as reported in Study 1, Chapter III (this monograph), children's secure base use was significantly associated with sensitive caregiving at Time 1 (r[79] ¼ 0.36, p < .001) and Time 2 (r[67] ¼ 0.34, p ¼ .003), after controlling for children's gender-the associations were virtually the same without controlling for gender, r(80) ¼ 0.38, p < .001 at Time 1; r(68) ¼ 0.36, p ¼ .002 at Time 2.…”
Section: Main Analysessupporting
confidence: 91%
“…It is also fair to say that "caregiver sensitivity" remains poorly defined. Still overwhelmingly referred to as maternal sensitivity, caregiver sensitivity is habitually used interchangeably with maternal responsiveness, caregiver-infant interaction quality, or mother-infant congruence and lacks grounding in universally accepted, clearly delineated, and specific behaviors (Bigelow et al, 2010;Meins, Fernyhough, Fradley, & Tuckey, 2001;Posada et al, 2016;Shin, Park, Ryu, & Seomun, 2008). Scholars largely agree that sensitivity should be considered a statement about the interaction between caregiver and infant, a highly complex phenomenon, and important aspect of parenting (van den Boom, 1997), but its operationalization is far from standardized.…”
Section: Evaluating Caregiver Sensitivity: Measures Mattermentioning
confidence: 99%
“…First, evidence from several separate studies (e.g., Meins, Fernyhough, Fradley, & Tuckey, 2001;Meins, Fernyhough, Arnott, Leekam, & DeRosnay, 2013;Meins et al, 2002) indicates that the concept of parental mind-mindedness is related to (but distinct from) that of parental sensitivity, which is typically defined as parents' ability to "tune in" and respond to the needs of their children. In turn, numerous studies (e.g., Bornstein et al, 1992;Bornstein, Putnick, Cote, Haynes, & Suwalsky, 2015;Posada et al, 2016) have shown that sensitive parental behavior and parent-infant contingent talk are culturally universal but vary in overall amount and quality across different cultural settings. A second reason for expecting cross-cultural contrasts in parental mind-mindedness is that, as noted earlier, cultures differ in the degree to which mental states are viewed as objects worthy of conjecture (Lillard, 1998).…”
mentioning
confidence: 99%